PENGENDALIAN KUALITAS UNTUK MENGURANGI JUMLAH PRODUK CACAT PADA PROSES PRODUKSI PLASTIK DENGAN METODE TAGUCHI - Salshabilla Nur Kusuma Putri (2021)
Quality is an important key to make loyal customers and reduce the return of defect products received by customers that led to high costs. So, the company must uphold their quality. This research took place at PT ABC that produces 2 types of plastics, HDPE and LDPE. The problem that occurred is there are still a large number of a not good product (NG) as a result from the production process. Based on these problems the researchers executed quality control to reduce defect products. First step is to identify the defect products using FMEA method, the highest RPN score will become the focus of the improvement. Then, the improvement will be analyzed using Fishbone Diagram. The results of the highest FMEA RPN are failure of thickness and width sizes that do not match specifications. This is due to sub-optimal machine settings, undisciplined operators, and quite a dirty work environment. From the results of the Taguchi method, it was found that the factors that had a significant effect were temperature and top rollers. Omit engine improvements, the optimum engine settings are at a temperature of 160, extruder 25.5, Upper Rollers 14.5, and Lower Rollers 13.5. Meanwhile, in human improvement, work environment and work methods, there is a result in evaluation of not good product (NG).